Waqf Perspective of Islamic Law and Law in Indonesia - Siregar, Syawal; Pane, Erwin (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2025)
This research aims to examine the concept and implementation of waqf according to the perspective of Islamic law and how it is regulated in the positive legal system in Indonesia. In Islam, waqf is seen as a charity whose rewards continue to flow as long as the benefits of waqf assets are still felt by the recipient. Meanwhile, in Indonesia, waqf is legally regulated through Law Number 41 of 2004 concerning Waqf and other implementing regulations. This research uses a qualitative method with a normative-juridical approach, namely examining the sources of Islamic law such as the Qur'an and Hadith as well as applicable laws and regulations. The results of the study show that the principles of waqf in Islamic law and laws in Indonesia have harmony, especially in terms of the eternity of waqf assets and their designation for the public good. However, there are some differences in terms of technical implementation and administration.